2014
DOI: 10.1039/c4cp01286k
|View full text |Cite
|
Sign up to set email alerts
|

Preference for a propellane motif in pure silicon nanosheets

Abstract: Free standing silicene nanosheets remain elusive presumably due to the instability associated with sp(2) hybridized silicon atoms. Here we show that silicon prefers nanosheets based on the non-classical Si5 unit with a [1.1.1]-propellane motif that has two inverted tetrahedral atoms bridged by three tetrahedral atoms. DFT calculations show that nanosheets constructed exclusively from propellane building blocks are consistently more stable than those with sp(2) silicon atoms or their hybrids. These nanosheets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
2
7
0
1
Order By: Relevance
“…They have shown that formation of the 3×3 structure on Ag(111) substrate was energetically favorable, but sending more Si atoms on top of this already formed 3×3 structure would transform it to a √ 3 × √ 3 structure through formation of dumbbell units. The dumbbell units were formed spontaneously whereby a new-coming Si atom would push one of the silicene atoms down and make the same connections itself on the top (Kaltsas and Tsetseris, 2013;Marutheeswaran et al, 2014). It is energetically favorable for dumbbell units to arrange themselves in a √ 3 × √ 3 honeycomb lattice and to shrink the lattice constant down to 0.64 nm which is exactly what was measured in experiments.…”
Section: A Brief History Of Silicenesupporting
confidence: 67%
“…They have shown that formation of the 3×3 structure on Ag(111) substrate was energetically favorable, but sending more Si atoms on top of this already formed 3×3 structure would transform it to a √ 3 × √ 3 structure through formation of dumbbell units. The dumbbell units were formed spontaneously whereby a new-coming Si atom would push one of the silicene atoms down and make the same connections itself on the top (Kaltsas and Tsetseris, 2013;Marutheeswaran et al, 2014). It is energetically favorable for dumbbell units to arrange themselves in a √ 3 × √ 3 honeycomb lattice and to shrink the lattice constant down to 0.64 nm which is exactly what was measured in experiments.…”
Section: A Brief History Of Silicenesupporting
confidence: 67%
“…They have shown that formation of the 3 3 structure on Ag(111) substrate was energetically favorable, but sending more Si atoms on top of this already formed 3 3 structure would transform it to a p 3 p 3 structure through formation of dumbbell units. The dumbbell units were formed spontaneously whereby a new-coming Si atom would push one of the silicene atoms down and make the same connections itself on the top (Kaltsas and Tsetseris 2013;Özçelik and Ciraci 2013;Marutheeswaran et al 2014). It is energetically favorable for dumbbell units to arrange themselves in a p 3 p 3 honeycomb lattice and to shrink the lattice constant down to 0.64 nm which is exactly what was measured in experiments.…”
supporting
confidence: 68%
“…Their topology is given in Chart 2 along with 2D space symmetry, conjugate directions, and important optimized interatomic distances. Though graphene oxide is not a monatomic 2D sheet, the 2D space symmetry is assigned for the idealized 2D sheet 32,33 to discriminate the environment of the epoxides succinctly. The other important geometrical parameters such as C−O bond S1).…”
Section: ■ Isomeric Sheets Of C 2 Omentioning
confidence: 99%